MedCare: a web-based clinic appointment system with Short Message Service (SMS) notification / Nur Elya Fhazlein Zamri and Mohd Nizam Osman - Fhazlein Zamri, Nur Elya; Osman, Mohd Nizam (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The MedCare Clinic Appointment System is a web-based application to manage appointments for patient and doctor at a non-government clinic. The purpose of implementing this system is to develop a web-based application which is enabling the patients request the appointments using cloud computing or online method before they get the doctor services in the clinic (face to face) as well as manage the appointment information such as schedule, rating, and notification through the system. The MedCare Clinic Appointment system also aims to reduce the time taken by patient to get the appointment within the doctor services. Furthermore, The MedCare Clinic Appointment system is integrated with Short Message Service (SMS) technology to notify the patient and doctor about the appointment status update.